Evaluation of Rapeseed-mustard Genotypes in Different Sowing Regimes and Their Genetic Variabilities - Islam, Md. Habibul; Salim, Muhammad; Hasan, Ahmed Khairul; Tabassum, Rehenuma; Ousro, Farhana Khatun; Hosen, Ishak; Dina, Mst Maiful Akter; Monshi, Fakhrul Islam (Journal of Tropical Crop Science, 2022)
Rapeseed-mustard is an important oilseed species with high nutritional and economic values; it’s popularity increases due to its diverse uses. Ten genotypes of rapeseed-mustard and two sowing dates were evaluated in a split plot design with three replications. Our study demonstrated that sowing dates and genotypes greatly influenced the growth parameters, yield, and it contributing characters. BARI sarisha-16 had the highest yield (1613 kg.ha-1) whereas Binasarisha-9 yielded the lowest yield (840 kg.ha-1). All the yield contributing characters was superior in the earlier (10 November, S1) sowing date than the 24 November (S2), demonstrated by the highest grain yield (1120 kg.ha-1) which was 10 % higher than the seed sown on 24th November (S2) (1025 kg.ha-1), and better higher vegetative growth. These results affirmed that the yield contributing traits resulted the higher seed yield. In most of the studied characters, the higher phenotypic variances were observed than that of its genotypic variances. The significant positive correlation with grain yield were found in plant height, number of primary branches/plants, number of siliqua/plants, siliquae length, number of seed per siliquae, days of 50% flowering to maturity and 1000 seed weight. Therefore, based on the yield and the related traits, BARI sarisha-16 can be used for further utilization.